An Evaluation of the Security Ability of the Basic Endowment Insurance System for China’s Urban and Rural Residents - Bing Liu; Yuhong He; Zhi Liu (Journal of Mathematics)
In this paper, security ability refers to the standard of evaluation that is used to measure the implementation performance of the basic endowment insurance system for China’s urban and rural residents (EIUR). To evaluate security ability, a three-level evaluation index system with a total of 19 indicators is designed. The research results show that it is low and even does not coincide with the country’s level of economic development, for the security ability of EIUR, due to the top-level design of the insurance system under analysis, the operating environment, and residents’ willingness to participate and contribute. Moreover, there are regional differences in regard to security ability; the development of various targets is not balanced. These findings suggest that it is necessary to promote the balanced development of various targets between regions and improve the completion of each target, especially in regard to “flexibility” and “fairness” targets.